2011
DOI: 10.3153/jfscom.2012004
|View full text |Cite
|
Sign up to set email alerts
|

The Aquatic and Semi-Aquatic Oligochaeta Fauna of Turkish Thrace

Abstract: In this study, freshwater Oligochaeta samples which were collected between the years 1985 and 1999 from different localities in Turkish Thrace were evaluated taxonomically. A total of 11 Oligochaeta species were determined. Also, all printed taxonomical studies on aquatic and semi-aquatic Oligochaeta fauna which were performed in Turkish Thrace until the present were discussed in this paper. As a result, it was gathered that a total of 37 species belonging Oligochaeta have been reported from Turkish Thrace. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…However, from Türkiye, only five species belonging to this subfamily have been reported so far: R. coccineus (Vejdovsky 1876) in Gümüş River by Öntürk and Arslan (2003); in Tunca River by Çamur-Elipek et al (2006); in Balıkdamı Wetland by Arslan et al (2007); in Lake Uluabat by Kökmen et al (2007); in Porsuk River and in the Trace Region by Arslan and İlhan (2010); in Trace Region- Taş et al (2012); in Tuzla Stream by Odabaşı et al (2018); Branchiura sowerbyi Beddard, 1892 in Buldan Dam Lake by Balık et al (2004); Monopylephorus irroratus (Verrill, 1873) in Hazar Lake by Şahin and Baysal (1972); Epirodrilus moubayedi Giani and Martinez-Ansemil (1981) in Balıkdamı Wetland by Arslan et al (2007); and Bothrioneurum vejdovskyanum Štolc, 1886 in Karamenderes Stream by Odabaşı et al (2017) have been reported from different parts of Türkiye.…”
Section: Introductionmentioning
confidence: 99%
“…However, from Türkiye, only five species belonging to this subfamily have been reported so far: R. coccineus (Vejdovsky 1876) in Gümüş River by Öntürk and Arslan (2003); in Tunca River by Çamur-Elipek et al (2006); in Balıkdamı Wetland by Arslan et al (2007); in Lake Uluabat by Kökmen et al (2007); in Porsuk River and in the Trace Region by Arslan and İlhan (2010); in Trace Region- Taş et al (2012); in Tuzla Stream by Odabaşı et al (2018); Branchiura sowerbyi Beddard, 1892 in Buldan Dam Lake by Balık et al (2004); Monopylephorus irroratus (Verrill, 1873) in Hazar Lake by Şahin and Baysal (1972); Epirodrilus moubayedi Giani and Martinez-Ansemil (1981) in Balıkdamı Wetland by Arslan et al (2007); and Bothrioneurum vejdovskyanum Štolc, 1886 in Karamenderes Stream by Odabaşı et al (2017) have been reported from different parts of Türkiye.…”
Section: Introductionmentioning
confidence: 99%
“…Homochaeta naidina Bretscher, 1896 Gediz S. (Balık et al 1999); Iúıklı L. ; Gediz Delta ; Nais alpina Sperber, 1948 (Öntürk & Arslan 2003); Lake District Region ; Küçük Menderes R. ); Yuvarlak R. (Yıldız et al 2007b); WBSL ; ; Uluda÷ GL (Ustao÷lu et al 2008); ; EHEBSL (Yıldız et al 2012); EHEBSL ; TTRR (Taú et al 2012); Adıgüzel DL (Özbek et al 2016 ; Lake District Region ; Yuvarlak R. (Yıldız et al 2007b); WBSL ; Uluda÷ GL (Ustao÷lu et al 2008); EHEBSL (Yıldız et al…”
mentioning
confidence: 99%
“…Aulodrilus limnobius Bretscher, 1899 Gediz Delta ; Yuvarlak R. (Yıldız et al 2007b); Sapanca L. (ùahin & Yıldız 2011); TTRR (Taú et al 2012); ;…”
unclassified